Paronychia: incidence during Magh Mela - Narain, Upma; Kant, Arun; Bajaj, Ashok Kumar (International Journal of Advances in Medicine, 2018)
Background: Paronychia is one of the most common infections of the fingers and toes. Clinically, paronychia present as an acute or a chronic condition. Methods: The retrospective study was carried out from January 2018 to February 2018 at Allahabad. Gram stain, ZN stain, KOH examination and culture were carried out in 230 cases and species identification was done by Vitek-2 system. Results: Out of these 230 cases 142 (61.73%) presented acute paronychia, 58 (25.21%) cases of chronic paronychia and the remaining 30 cases (13.06%) did not show any growth. In the cases of acute paronychia, authors identified 53.52% Staphylococcus aures, 15.49% Staphylococcus saprophyticus, 2.82% Micrococci and 6.34% Citrobacter among aerobes while among anaerobes authors isolated 5.63% Peptococcus, 8.45% Peptostreptococcus, 3.52% Bacteroides and 4.23% Fusobacterium. Among chronic paronychia authors recorded 48.28% pure bacterial growth, 18.97% pure fungal growth, 20.69% mixed bacterial infections and 12.07% mixed bacterial and fungal infections. Conclusions: From this study authors conclude that cold weather and humidity were the predominant and predisposing factors of the high incidence of acute paronychia. Due to very short span single pathogen was isolated from the lesions. In cases of chronic paronychia 37.76% mixed infection were also recorded which may be due to super aided infections with primary pathogen.